Modernizing thermal discharge assessments for the 21st century. (22nd July 2021) - Barnthouse, Lawrence W.; Coutant, Charles C.
Abstract: A jointly prepared, interagency (US Environmental Protection Agency [USEPA] and the US Nuclear Regulatory Commission [USNRC]), §316(a) Technical Guidance Manual has been the primary guide to ecological studies of thermal discharges at power plants since 1977. It reflected contemporary ecological theory, which assumed that undisturbed populations and ecosystems possessed a balanced and relatively unchanging structure and function that could be disrupted by addition of heat from a thermal discharge. It was intended primarily to facilitate the licensing of proposed nuclear power plants and thus focused on predictive assessments. Since 1977, however, scientific and regulatory contexts of §316(a) assessments have changed. Ecologists abandoned the notion of "balance" in populations and ecosystems and now recognize that natural systems are always changing spatially and temporally. Regulatory emphasis has shifted from predictive assessments at new plants, largely based on thermal‐tolerance laboratory data, to retrospective assessments based on field data at operating plants. We suggest updates to thermal‐assessment studies based on modern ecological theory and recent thermal‐assessment practice. The concepts we outline are fully consistent with statutory language and may assist in design and implementation of study plans by applicants and their consultants, development of discharge permits by USEPA or state agencies, and reviews of assessment documents by interested public and environmental organizations. Integr Environ Assess Manag 2022;18:459–468. © 2021 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). KEY POINTS: The 1977 EPA guidance on thermal effects assessment employed an outdated definition of the concept of "balance." The guidance was also directed at predictive assessments of potential effects at power plants that had not yet been built. We develop a revised definition of the term "balanced indigenous population" that is consistent with modern ecological theory. We also provide recommendations for the design of thermal effects studies at existing power plants using site‐specific ecological data.